1989
DOI: 10.1128/aac.33.12.2083
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of fluorinated nucleoside analogs and their synergistic effect in combination with phosphonoformate against human immunodeficiency virus type 1

Abstract: One hundred nucleoside analogs with fluorine substitutions at various positions on the pentose ring were evaluated for inhibitory activity against human immunodeficiency virus type 1 (HIV-1). Nine compounds emerged as inhibitors of HIV-1 replication, with various degrees of selectivity; the most active of these was 3'-fluoro-3'-deoxythymidine, followed by 5'-amino-3'-fluoro-3'-deoxyadenosine. Substitution of fluorine at the 2'-deoxy or 3'-deoxy position resulted in increased antiviral activity of the thymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Animal models of HIV infection have only recently become available, the clinically most relevant probably being infection of macaque monkeys with the simian immunodeficiency virus (SIV) (5,13) or with HIV type 2 (HIV-2) (16). The effects of zidovudine and 3'-fluoro-3'-deoxythymidine (FLT) on HIV-1 in vitro (9) and on SIV-infected monkeys in vivo (12) were recently investigated, and it was found that FLT is approximately 10 times more potent than zidovudine. The pharmacokinetic properties of FLT are similar to those of zidovudine in monkeys, the most important difference being that FLT is not protein bound (12).…”
mentioning
confidence: 99%
“…Animal models of HIV infection have only recently become available, the clinically most relevant probably being infection of macaque monkeys with the simian immunodeficiency virus (SIV) (5,13) or with HIV type 2 (HIV-2) (16). The effects of zidovudine and 3'-fluoro-3'-deoxythymidine (FLT) on HIV-1 in vitro (9) and on SIV-infected monkeys in vivo (12) were recently investigated, and it was found that FLT is approximately 10 times more potent than zidovudine. The pharmacokinetic properties of FLT are similar to those of zidovudine in monkeys, the most important difference being that FLT is not protein bound (12).…”
mentioning
confidence: 99%
“…FLT was phosphorylated better than AZT in all three cell types, despite the lower concentration of FLT used, which is presumably the basis for the higher antiviral activity and higher toxicity of FLT compared to AZT (Balzarini et al, 1988;Hartmann et al, 1988;Matthes et al, 1988;Bazin et al, 1989;Koshida et al, 1989a).…”
Section: Discussionmentioning
confidence: 99%
“…* P < 0.005 compared to uninfected H9 cells ** P < 0.001 compared to uninfected H9 cells dNTP pools of GEM,H9, The dNTP pools of GEM, H9, and HIV-infected H9 cells (Koshida et al, 1989a), AZT and castanospermine (Johnson et aI., 1989), AZT and 9-(2-phosphonylmethoxyethyl)-adenine (Smith et al, 1989), and AZT and dipyridamole (Szebeni et et., 1989). We also showed the combination of AZT and FLT to be synergistic against HIV replication in cell culture (Harmenberg et al, 1990a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations